Health-related quality of life and cognitive functioning in survivors of oligodendroglioma: an international cross-sectional investigation - Boele, Florien W; Frances, Sé M; Darlix, Amélie; Ducray, Francois; Cartalat, Stéphanie; Guerdoux, Estelle; Tabouret, Emeline; Burger, Michael C; Rydén, Isabelle; Malmstrom, Annika; Vauleon, Elodie; Kazda, Tomas; et al. (Neuro-oncology (Charlottesville, Va.), 2025)
Patients with oligodendroglioma have a relatively favourable prognosis. The long-term impacts of the tumour itself and its treatment on health-related quality of life (HRQOL) and cognition remain largely unclear. We investigated associations between treatment and functioning of survivors of oligodendroglioma. In this cross-sectional observational study, patients with oligodendroglioma, isocitrate dehydrogenase-mutant and 1p/19q-codeleted, diagnosed ≥5 years ago, were recruited. Patients completed patient-reported outcome measures (EORTC QLQ-C30; BN20; MOS Cognitive Complaints Scale) and cognitive tests (HVLT-R, TMT, COWAT). Associations between HRQOL and cognition outcomes, and clinical variables (time since diagnosis; age at diagnosis; progression; tumour location; treatments delivered; time since treatment; current medication;) were explored with regression analyses. In total, 237 patients M=9.9 years post-diagnosis (sd=4.2, range 5.0-25.8) took part from 33 sites across 9 countries. Clinically relevant levels of impairment were noted in >40% of patients on EORTC QLQ-C30 scales for cognitive functioning (56.1%), emotional functioning (49.8%), fatigue (45.1%), and physical functioning (40.5%). In individuals, cognitive impairment ranged from 17.7% for processing speed to 46.0% for episodic verbal memory (delayed recall). Among other clinical factors such as current use of antiseizure medication or antidepressants, age, disease progression, time since diagnosis and time since treatment, and radiotherapy treatment (ever received) was linked to HRQOL and cognitive functioning outcomes (post-hoc analyses for cumulative radiotherapy dose: not significant). In oligodendroglioma survivors, HRQOL and cognitive impairment are prevalent even years into follow-up. Supportive care and rehabilitation should be prioritized to mitigate these challenges and improve daily functioning. NCT04708548.